Usage of Jatropha curcas as Botanical Insecticide in Controlling Insect Pest - Asmanizar (Jurnal Online Pertanian Tropik, 2023)
Insect pests can cause damage to plants and cause losses. Insect pests on plants need to be controlled both preventively and curatively. Integrated control is an integration of several control methods that can be implemented in a compatible and comprehensive. Insect pest control using bio-active plant materials as an alternative to synthetic chemicals. Plants produce secondary metabolite compounds that can affect insects, including Jatropha curcas (Euphorbiaceae). Studies on several insect pests both in the laboratory and in the field against insect pests that attack the field and agricultural product storage warehouses have been carried out to determine their effectiveness. Jatropha curcas plants/parts of plant were applied after extraction treatment with various solvents (water, ethanol, methanol, acetone, petroleum ether, n-hexane and chloroform) or direct use. The results showed that J. curcas exhibited control effects against several types of insect pests from various insect pest. Laboratory study showed the insecticidal effect of J. curcas against Helicoverpa armigera, Spodoptera frugiperda, Plutella xylostella, Earias insulata, Spilarctia oblicua, Tuta absulata, Nezara viridula, Corcyra cephalonica, Maruca vitrata. Field study showed population reduction of Putella xylostella and Aphis craccivora. Whilst, on stored product study showed mortality of insect pest (Sitophilus zeamais, Rhyzopertha dominica, Callosobruchus chinensis and C. maculatus) and reduction of weight loss of stored products. Jatropha curcas has the potential as a pest insect control to be integrated into the IPM component. Keywords: Jatropha curcas, Botanical insecticide, Insect pest